Sistem Pendukung Keputusan Pemilihan Lingkungan Rumah Sehat dengan Metode Analytical Hierarcy Process (AHP) dan Simple Multi Attribute Rating Technique (SMART) - Muhammad Azroni Azroni; Berto Nadeak (Bulletin of Computer Science Research, 2021)
Home environment is one of the most important buildings for humans, namely as a place of shelter and rest as well as a means of family development. Having a healthy home can foster a healthy life physically, mentally and socially, so that all members can work productively. people are competing to build houses with different advantages and disadvantages so that sometimes they do not meet health requirements. To improve a healthy home, in this case the responsibility of the head of the environment is also getting bigger. In order to motivate the head of the environment to always ensure that the home environment is always healthy in his area, a selection of a healthy home environment is made in a village. The problem that has occurred so far is that the decisions made by the village head towards a healthy home environment are still personal, not based on objectivity, in making decisions. This is a problem in choosing a healthy home environment. In order for the decision of the head of the village to be better, a decision support system (SPK) is needed. So in this study a Decision Support System (DSS) will be made using the AHP and SMART methods, which are expected to help consumers in determining the selection of a healthy home environment. precisely and quickly from several existing criteria and alternatives. Namely the weighting AHP method and the SMART ranking method.